Thermal properties and kinetic analysis of pyrolysis products of nicotine salts from e-cigarettes using pyrolysis-gas chromatography/mass spectrometry - Yang, Ji; Li, Yirong; Liu, Chunbo; Tang, Shiyun; Li, Zhengjie; Jiang, Lihong (Frontiers in Environmental Science, 2023)
Volatile organic chemicals (VOCs) released from e-cigarette is a special source of air pollutants. In this work, we have investigated the VOCs released from six nicotine salts (i.e., nicotine benzoate, nicotine tartrate, nicotine citrate, nicotine malate, nicotine lactate, nicotine levulinate) that are commonly used in e-cigarette. Pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) method and thermogravimetric method were used to analyze the thermogravimetric characteristics and product release behavior of different nicotine salts. Moreover, the kinetic models and thermodynamic parameters of nicotine salts during thermal decomposition process were obtained. Thermogravimetric characteristic parameters of six nicotine salts were significant differences. By use of Py-GC/MS, our data showed that the pyrolysis products of nicotine salts were mainly from nicotine, acid anhydrides, carboxylic acids, n-heterocycles, while more than 90% of the nicotine of citrate, tartrate, and malate were transferred to smoke. The result revealed that activation energies of the nicotine salts range from 21.26 to 74.10 kJ mol-1, indicating that the pyrolysis of the nicotine salts is non-spontaneous heat absorption process, and the organic acid was the key factor affecting the release of nicotine to ambient air.